The Effect of Chronic Exposure of Graphene Nanoplates on the Viability and Motility of A549 Cells - Šestáková, Blanka; Schröterová, Ladislava; Bezrouk, Aleš; Čížková, Dana; Elkalaf, Moustafa; Havelek, Radim; Rudolf, Emil; Králová, Věra (Nanomaterials (Basel, Switzerland), 2022)
Graphene and its derivatives are popular nanomaterials used worldwide in many technical fields and biomedical applications. Due to such massive use, their anticipated accumulation in the environment is inevitable, with a largely unknown chronic influence on living organisms. Although repeatedly tested in chronic in vivo studies, long-term cell culture experiments that explain the biological response to these nanomaterials are still scarce. In this study, we sought to evaluate the biological responses of established model A549 tumor cells exposed to a non-toxic dose of pristine graphene for eight weeks. Our results demonstrate that the viability of the A549 cells exposed to the tested graphene did not change as well as the rate of their growth and proliferation despite nanoplatelet accumulation inside the cells. In addition, while the enzymatic activity of mitochondrial dehydrogenases moderately increased in exposed cells, their overall mitochondrial damage along with energy production changes was also not detected. Conversely, chronic accumulation of graphene nanoplates in exposed cells was detected, as evidenced by electron microscopy associated with impaired cellular motility.
Keywords: long-term cultivation; nanomaterials; pristine graphene; in vitro; toxicity; mitochondrial metabolism; graphene accumulation; cell migration